Study of thermal comfort in the city of são paulo using ENVI-met model - Carfan, Ana Claudia; Galvani, Emerson; Nery, Jonas Teixeira [UNESP] (My University, 2012)
This study is aimed to analyze the thermal comfort in different areas in the city of São Paulo. Two different areas were selected, a densely built (Consolação district) and the other was Fontes do Ipiranga State Park (FISP), an area with only a few buildings and reduced impermeability. A micro-climatic ENVImet was used to simulate the interaction surface-atmosphere in the urban environment. The model resolution is between 0.5 and 10m. This model was developed by Bruse and Fleer (1998) and Bruse (2004). Through the thermal comfort index PMV (predicted mean vote) and MRT (mean radiant temperature) provided by the model, it revealed that the State Park displays PMV values close to comfortable compared to the other studied area. The analysis of thermal comfort index and the Wind flow showed the influence of high buildings in the local climatic environment.
Keywords: ENVI-met; Thermal comfort; Urban climate; building; heat island; microclimate; numerical model; urban climate; Brazil; Sao Paulo [Brazil]; Sao Paulo [Sao Paulo (STT)]; Papaya mosaic virus